Вы находитесь на странице: 1из 5

# Homework 1

Page 12 of Rosenlicht: 2, 3, 4, 5, 7, 8.
2. If A is a subset of the set S, show that
(a) (Ac )c = A;
(b) A A = A A = A = A;
(c) A = ;
(d) A = .

Solution:
(a) Let x (Ac )c . Then x
/ Ac , which is the same as x A, and so (Ac )c A. If x A,
then x
/ Ac , and so x (Ac )c , which gives A (Ac )c . These two containments prove
that A = (Ac )c .
(b) We clearly have that A A A. Suppose that a A A, then a A or a A,
which, in either case gives that a A and A A A, and so A A = A. We also clearly
have that A A A. Let a A, then we have that a A and a A, so a A A, and
so A A A. This proves A A = A. A = A is similar to (c), so we omit it from
the solutions.
(c) We have that A by definition. Let a A , then a A and a . This
gives that A .
(d) This is similar to (c) as well, and we omit the solution.
3. Let A, B, C be subsets of S. Prove the following statements
(a) Ac B c = (A B)c ;
(b) A (B C) = (A B) (A C);
(c) A (B C) = (A B) (A C);

Solution:
(a) Let x (A B)c and so x
/ A B. This means that either x A and x
/ B or
c
x
/ A and x B. If x A and x
/ B, then x A and x B . So we have that
c
c
c
x A B . Similarly, if x A and x B, then we have x Ac B c . This gives that
(A B)c Ac B c .
Suppose that x Ac B c , then x Ac or x B c . Consider the situation where
x Ac . If x B then x
/ A B, or equivalently x (A B)c . If x B c , then we have
that x
/ A B as well and so x (A B)c , giving that Ac B c (A B)c . The case
when x B c is handle similarly.
(b) Let x A(B C). Then x A and x B C. So we have that x A and x B or
x C. If x B, then we have that x A B, and so A (B C) (A B) (A C).

## Similarly, if x C, then we have that x AC and so A(BC) (AB) (AC). In

either case we have A(BC) (AB)(AC). Suppose now that x (AB)(AC).
Then we have that x A B or x A C. This says that x A and x B or x A
and x C, or x A and x B of x C, giving x A (B C). This gives that
(A B) (A C) A (B C).
(c) This can be done similarly to (b). Alternatively, one can use (a) and (b) applied to
compliments of sets.
4. The solution to this is similar to Problem 3. Exact details are left to the student.
5. Let I be a non-empty set and for each i I, let Xi denote a set. Then
(a) B iI Xi = iI B Xi ;
(b) (iI Xi )c = iI Xic .

Solution:
(a) If x B iI Xi then x B and x iI Xi . Since x iI Xi , there exists an
i0 I such that x Xi0 . So x B Xi0 , and hence x iI B Xi . This gives
B iI Xi iI B Xi . If x iI B Xi , then there exists a i0 I such that
x B Xi0 . This gives that x B and x Xi0 , which implies that x B and
x iI Xi . So we have that x B iI Xi , and iI B Xi B iI Xi .
(b) If x (iI Xi )c , then x
/ iI Xi , so there exists no i I such that x Xi . But,
this means that i I x Xic , and so x iI Xic . This gives (iI Xi )c iI Xic . On
the other hand, if x iI Xic then for all i I x Xic . This means that for all i I
x
/ Xi . So there exists no i I such that x Xi , and so x 6 in(iI Xi )c . This gives the
containment iI Xic (iI Xi )c .
7. Let f : X Y be a function and let A and B be subsets of X and C and D subsets of
Y . Prove that
(a) f (A B) = f (A) f (B);
(b) f (A B) f (A) f (B);
(c) f 1 (C D) = f 1 (C) f 1 (D);
(d) f 1 (C D) = f 1 (C) f 1 (D);
(e) f 1 (f (A)) A;
(f) f (f 1 (C)) C.

Solution: We wont provide the solution to all of these since they are similar. We instead just do a couple of them.
(a) Let y f (A B), then there exists x A B such that f (x) = y. Since x A B,
then x A or x B. If x A, then y = f (x) f (A), and so y f (A)f (B). Similarly,
if x B, then we have that y f (A)f (B). Thus, we have that f (AB) f (A)f (B).
Suppose now that y f (A) f (B). Then y f (A) or y f (B). If y f (A), then
there is an x A such that y = f (x). But, if x A, then x A B, and so
y = f (x) f (A B). The same reasoning can be repeated if y f (B). Thus, we have
that f (A) f (B) f (A B).
(c) Suppose that x f 1 (C D), then there exists y C D such that f (x) = y. Since
y CD, then y C and y D and so x f 1 (C) and x f 1 (D), giving x f 1 (C)
f 1 (D). Now suppose that x f 1 (C) f 1 (D), or f 1 (C D) f 1 (C) f 1 (D);.
Then x f 1 (C) and x f 1 (D), or f (x) C and f (x)x D. So we have that
f (x) C D, and thus x f 1 (C D). This gives that f 1 (C D) f 1 (C) f 1 (D).
(e) Let a A, then f (a) f (A). But, this immediately gives that a f 1 (f (A)).
8. Under the assumptions of Problem 7, prove that f is one to one if and only if in (e)
can be replaced by = for all A X, and f is onto if and only if the sign in (f) can be
replaced by = for all C Y .
Solution: Suppose that we have f 1 (f (A)) = A for all A X. We need to show
that f is one-to one. Let A = {a}, a set with just one element. Then we have that
{a} = f 1 ({f (a)}). If f is not one-to-one, then there exists a1 6= a2 A such that
f (a1 ) = f (a2 ). Note that we then have that {a1 } =
6 {a2 } and {f (a1 )} = {f (a2 )}. But
we then have that
{a1 } = f 1 ({f (a1 )}) = f 1 ({f (a2 )}) = {a2 }
but this is a contradiction since {a1 } =
6 {a2 }, and so f is one-to-one.
Suppose now that f is one-to-one. By 7(e) we have that
f 1 (f (A)) A
and so we only need to show that f 1 (f (A)) A. Let x f 1 (f (A)), then we have
that f (x) f (A). Since f (x) f (A), there exists an a A such that f (x) = f (a).
However, since f is one-to-one, we have that x = a. Thus, we have that x A, proving
that f 1 (f (A)) A.
1. For each k N let Ak be a countable set. Show that

[
k=1

Ak

## is countable. In other words, a countable union of countable sets is countable.

Solution: Since Ak is countable, we have can arrange them in a sequence a1k , a2k , a3k , . . ..
Then we write these sequences in the following way
a11 a21
a12 a22
a13 a23
..
..
.
.
1
ak a2k
..
..
.
.

a31 a41
a32 a42
a33 a43
..
..
.
.
3
ak a4k
..
..
.
.

..
.

..
.

S
Define : N
k=1 Ak by following the zig-zag path starting in the upper left corner
and then filling out the diagonals perpendicular to the main diagonal. Namely, (1) = a11 ,
(2) = a21 , (3) = a12 , (4) = a13 , . . .. If is clear that is a bijection.
2. Prove that the map f : A B is a bijection if and only if there exists a map g : B A
such that g f = IdA and f g = IdB . Show also that g = f 1 and is uniquely determined.

## Solution: If f is a bijection, then we have that g = f 1 and that f 1 f = IdA and

f f 1 = IdB . Suppose now that there exists a map g : B A with the desired
properties. First, observe that f is onto. Let b B, and set a = g(b). Then we have that
f (a) = f (g(b)) = b. Next, we observe that f is one-to-one. Suppose that a1 6= a2 , then
we claim that f (a1 ) 6= f (a2 ) as well. If it was the case that a1 6= a2 and f (a1 ) = f (a2 ),
then we would have that a1 = g(f (a1 )) = g(f (a2 )) = a2 , which would be a contradiction.
To see that g is uniquely determined, suppose that there are two maps g1 : B A
and g2 : B A, then we claim that g1 (b) = g2 (b) for all b B.
3. Let f : A B and g : B C be bijections.
(g f )1 = f 1 g 1 .

## Solution: It is easy to see that for the function h = f 1 g 1 : C A we have satisfies

h (g f ) = IdA and (g f ) h = IdC and so by Problem 2 above we have that g f is
a bijection and that (g f )1 = f 1 g 1 .
4. Let A = {A } be a collection of subsets of a set S. Prove the following two statements:
S
T
(a) S \ A = S \ A ;
T
S
(b) S \ A = S \ A .

Solution: Part (a) is simply 5(b) from above. To see that (b) holds, let B = Ac . By
part (a), we have
!c
[
\
B = (B )c

set, so we have
[

which is (b).

Bc

!c !c

Ac =

B =

!c
=